y=2x so replacr the -y with -2x so 2x+6 is 8x. :)
15 + 6(x + 1)
Factor a 3 out of the expression.
3(5 + 2(x + 1))
Distribute the 2.
3(5 + 2x + 2)
Combine like terms.
3(7 + 2x)
3(7 + 2x) is your answer.
Answer:
12, 43/63
Step-by-step explanation:
Answer:
= 17 v^2 + 7v + 11
Step-by-step explanation:
Given that:
= (8v^2+6v+5)+(9v^2+v+6)
by removing brackets
= 8v^2 + 6v + 5 + 9v^2 + v + 6
Addin like terms:
= (8v^2 + 9v^2) + (6v + v)+ (5 + 6)
= 17 v^2 + 7v + 11
I hope it will help you!
Answer:
1. Isolate
2. Closed
3. Reversed
If you have more problems with things similar to this, I recommend this website, it gives a detailed description on how to solve the equations:
https://www.mathsisfun.com/algebra/inequality-solving.html